2008
DOI: 10.1001/archpedi.162.7.682
|View full text |Cite
|
Sign up to set email alerts
|

Why Young Adults Hold the Key to Assessing the Obesity Epidemic in Children

Abstract: Despite significant increases in prevalence rates of childhood obesity in the United States during the past 2 decades, rates of type 2 diabetes mellitus among children at the population level have not followed a similar trajectory as those in adults. In this review, hypotheses for the contrasting findings in children compared with adults are explored, as are possible links between the trends in childhood obesity rates and increases in type 2 diabetes among young adults in the United States. This review conclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 63 publications
0
30
0
Order By: Relevance
“…Din-Dzietham et al 7 reported that a time lag may exist between the rise in obesity and the rise in BP. Although biological mechanisms could explain a time lag between the rise in obesity and type 2 diabetes (eg, long latency between an early stage of insulin resistance and the failure of insulin secretion by the pancreatic ␤ cells 33 ), BP rapidly changes in response to weight change at the individual level. 34 Other epidemiological data in adults did not systematically reveal the expected relation between the obesity trends and mean BP.…”
Section: Discussionmentioning
confidence: 99%
“…Din-Dzietham et al 7 reported that a time lag may exist between the rise in obesity and the rise in BP. Although biological mechanisms could explain a time lag between the rise in obesity and type 2 diabetes (eg, long latency between an early stage of insulin resistance and the failure of insulin secretion by the pancreatic ␤ cells 33 ), BP rapidly changes in response to weight change at the individual level. 34 Other epidemiological data in adults did not systematically reveal the expected relation between the obesity trends and mean BP.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Because obesity is associated with cardiovascular disease, type 2 diabetes, nonalcoholic fatty liver disease (NAFLD), hypertension and several types of cancer including cancers of the colon, kidney and pancreas, early prevention of obesity has become of great importance. 3,4 Thus, to identify the factors for the pathogenesis of obesity and to develop methods for diagnosing obesity and its associated diseases at an early stage for their prevention are urgent issues.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a risk factor for insulin resis- tance and pancreatic β-cells are likely to secrete more insulin when compensating for insulin resistance. The dysfunction of β-cells may cause pre-diabetes, a condition ultimately leading to diabetes (32). Notably, the mtDNA genome assay detected a heteroplasmic mtDNA mutation A8890G in the patient and was not observed in other members of the family.…”
Section: Discussionmentioning
confidence: 87%